A new record of Bengalia emarginata Malloch, 1927 (Diptera: Calliphoridae) from Malaysia - Chin, H.C.; Kurahashi, H.; Marwi, M.A.; Jeffery, J.; Dhang, C.C.; Zuha, R.M.; Omar, B. (2008)
During a forensic entomological study conducted at an oil palm plantation in Tanjung Sepat, Kuala Langat, Selangor, a. Bengalia emarginata Malloch, 1927 (Diptera: Calliphoridae: Calliphorinae: Bengalini) was collected for the first time. Two adults were collected nearby the pig carcass by the first author and identified by the second. Prior to this finding, nine species of Bengalia were recorded from peninsular Malaysia or Borneo. Male of B. emarginata are different from Bengalia varicolor Fabricious by the following characters: Sternite 5 projection rounded with small identation and mid tibia double-fringed in ventral surface.